DIGITAL TOURISM DEVELOPMENT STRATEGY AS A PROMOTION OF CREATIVE ECONOMY TOURISM IN BANTEN PROVINCE - April Laksana; Kenedi, Kenedi; Basuki Rakhim Setya Permana (SEAN Institute, 2022)
The tourism sector is one sector that has great potential to increase state and regional income. For this reason, efforts are needed to develop tourism in Indonesia. One of the programs from the government to increase the number of tourists is to prioritize tourism development in 10 locations, one of which is Tourism in Banten Province. In addition to developing tourism areas, another thing that can be done to increase the number of tourists is using information technology as a promotional medium through Digital Tourism. The purpose of this study is to view and analyze digital tourism as tourism promotion in Banten Province as a way of promoting tourism in Banten Province. The analytical technique used in this study is a SWOT analysis technique by looking at internal factors (strengths and weaknesses) and external factors (opportunities and threats) related to the development of Digital Tourism in Banten Province. The results of this study can be used by the government or related parties in determining the direction of tourism development in Banten Province